Drospirenone–Ethinyl Estradiol and Cyproterone Acetate in Moderate Severe Acne with Hyperandrogenism: A Randomized Double-Blind Trial - Gunardi, Eka Rusdianto; Bernadette, Irma; Kurniawan, Riyan Hari; Noviani, Astri (Indonesian Socety of Obstetrics and Gynecology, 2026)
ABSTRACT Background: Acne vulgaris is a health problem experienced by 85% of people in Indonesia. The highest prevalence is in women, who attempt to treat acne vulgaris. Unsuccessful acne vulgaris therapy is associated with hormonal influences, the stimulation of the sebaceous glands by androgen hormones. Hyperandrogenism is experienced by 10% of women in Indonesia. The main therapy for hyperandrogens is ciproterone acetate. Drospirenone combined with ethinyl estradiol, apart from sparing pregnancy, is also thought to be effective in treating clinical symptoms of hyperandrogenism. Currently, there is no study on drospirenone for acne and hyperandrogen therapy in Indonesia. Objective: Determine the efficacy of treatment combination 3-mg drospirenone and 20-microgram ethinyl estradiol as management of choice for moderate-severe acne vulgaris and symptoms of hyperandrogenism (hirsutism, secondary amenorrhea, and oligomenorrhea) for 3 cycles. Method: A randomized clinical trial with a double-blind study was done. Consecutive sampling is based on a random allocation table. A total of 42 subjects were diagnosed with moderate-severe acne vulgaris with hirsutism, secondary amenorrhea and/or oligomenorrhea at RSCM, divided into 2 groups, 21 subjects using drospirenone 3 mg combined with 0.030 mg ethinyl estradiol (DRSP/EE) and 21 subjects using 2 mg ciproterone acetate and 0.035 mg ethinyl estradiol (CRPN/EE), followed with examination of free testosterone check in laboratory. There was 1 subject who dropped out (Cyproterone group). The duration of therapy was 3 months then evaluation of acne lesions, Ferriman Gallwey score (FG score), and menstrual period. Results: Characteristics of study subjects with the majority of subjects aged 25-35 years, 51,3%. The education level of most subjects about 57,1%, was a bachelor's degree. Testosterone levels at the start of the study were 1,41±0,64 for the DRSP/EE group and 1,32±0,48 for the CRPN/EE group. For the degree of acne, 85.7% of subjects using DRPS/EE and 85% of subjects using CPRN/EE had reduced acne lesions with a P value of 0.645. For hirsutism by calculating the FG score, 61.9% of the subjects using DRSP/EE and 50% of the subjects consumed CPRN/EE had a decreased FG score with a value of P value 0.443, and their menstrual period became regular for 85.7% of the subjects using DRSP/EE and 90% of the subjects using CPRN/EE with P value 0.645. Conclusion: Drospirenone and ethinyl estradiol are as effective as cyproterone acetate combined with ethyl estradiol as treatment of moderate to severe acne vulgaris, hirsutism, secondary amenorrhea, and oligomenorrhea. Keywords: acne vulgaris, cyproterone acetate, drospirenone, hirsutism, secondary amenorrhea